2014
DOI: 10.1039/c3cp54936d
|View full text |Cite
|
Sign up to set email alerts
|

Micro- or nanorod and nanosphere structures derived from a series of phenyl-porphyrins

Abstract: We examine here a series of meso-phenyl porphyrin micro- and nanostructures. Optical absorption and emission spectroscopy imaging and atomic force microscopy are used to investigate the effect of peripheral groups in nano- and microstructures of 5,10,15,20-tetraphenylporphyrin (H2TPP) compared to three other phenylporphyrins, i.e. 5,10,15-triphenylporphyrin (H2-Tri-PP), 5,10-diphenylporphyrin (H25,10-BPP) and 5,15-diphenylporphyrin (H25,15-BPP) molecules. We show that nanospheres and nanorods are formed, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 49 publications
(71 reference statements)
3
10
0
Order By: Relevance
“…Cellulose absorbs UV light as shown in the UV–vis spectrum consisting of a broad peak centered around 322 nm, in agreement with data previously reported in the literature. , Both TMPyP and TPP are characterized by a broad, high-intensity Soret band and four lower-intensity Q bands in the UV–vis spectrum . Upon addition of the porphyrins to the CNF substrate, the peak associated with cellulose becomes less prominent and the Q and Soret become slightly red-shifted, suggesting possible J -aggregation of the molecules on the cellulose substrate. , Figure f shows the FTIR spectra of TMPyP in powder form and on CNF compared to the CNF substrate only. The spectrum of TMPyP is characterized by peaks at 713 cm –1 (N–H bending), 793 cm –1 (C–H bending), 1456 and 1402 cm –1 (C–N stretching and bending), 1559 cm –1 (CC stretching), as well as 1637 cm –1 (CN stretch vibration of pyridyl rings). , Upon the addition of the porphyrin solution on cellulose nanofibers, peaks associated with the porphyrin could not be distinguished in the spectrum.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Cellulose absorbs UV light as shown in the UV–vis spectrum consisting of a broad peak centered around 322 nm, in agreement with data previously reported in the literature. , Both TMPyP and TPP are characterized by a broad, high-intensity Soret band and four lower-intensity Q bands in the UV–vis spectrum . Upon addition of the porphyrins to the CNF substrate, the peak associated with cellulose becomes less prominent and the Q and Soret become slightly red-shifted, suggesting possible J -aggregation of the molecules on the cellulose substrate. , Figure f shows the FTIR spectra of TMPyP in powder form and on CNF compared to the CNF substrate only. The spectrum of TMPyP is characterized by peaks at 713 cm –1 (N–H bending), 793 cm –1 (C–H bending), 1456 and 1402 cm –1 (C–N stretching and bending), 1559 cm –1 (CC stretching), as well as 1637 cm –1 (CN stretch vibration of pyridyl rings). , Upon the addition of the porphyrin solution on cellulose nanofibers, peaks associated with the porphyrin could not be distinguished in the spectrum.…”
Section: Resultssupporting
confidence: 89%
“…36 Upon addition of the porphyrins to the CNF substrate, the peak associated with cellulose becomes less prominent and the Q and Soret become slightly red-shifted, suggesting possible Jaggregation of the molecules on the cellulose substrate. 37,38 Figure 1f shows the FTIR spectra of TMPyP in powder form and on CNF compared to the CNF substrate only. The spectrum of TMPyP is characterized by peaks at 713 cm −1 (N−H bending), 793 cm −1 (C−H bending), 1456 and 1402 cm −1 (C−N stretching and bending), 1559 cm −1 (CC stretching), as well as 1637 cm −1 (CN stretch vibration of pyridyl rings).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Based on the above results from TEM, UV/Vis, and fluorescence spectra, a possible mechanism was proposed (Scheme ). When H 2 TPP‐POSS self‐assembled at a concentration below 10 −4 M , vesicular morphologies were formed by the driving force of H‐type π‐electronic stacking between TPP moieties 5b. 14 In addition, the three‐dimensional POSS moieties also play an essential role in the formation of vesicles and exist both inside and outside of the vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…In case of thiacarbocyanine aggregates the excitation polarization was varied, a stronger emission with polarization along the fiber axes was observed, and it was concluded that the long axis of the molecule is aligned along the fiber axes [9]. Just slightly different exciton life times were reported for rod-and sphere shaped porphyrin aggregates [10]. As a first step to answer the question which types of excitations are present and how they depend on structural features and the environment, we investigate morphology, fluorescence, and phosphorescence of porphyrin aggregate structures by correlative microscopy methods.…”
Section: Introductionmentioning
confidence: 98%